Odpowiedzi

2010-01-24T14:31:36+01:00
A) -(x+2y-3z+4)-3x-4y+5z-2)+(4y-y+5z-1) = -x - 2y + 3z -4 -3x + 4y - 5z +2 + 4y + 5z - 1 = -4x + 6y + 7z -3

b)2*(3x+2y-4z+5)+3(5x-8y+2z-1)+(4x-2y+7z+8) = 6x + 4y - 8z + 10 + 15x - 24y + 6z - 3 + 4x-2y+7z+8 = 25x - 22y + 9z +15
2010-01-24T19:42:39+01:00
A)
-(x+2y-3z+4)-3x-4y+5z-2)+(4y-y+5z-1)=
-x-2y+3z-4-3x-4y+5z-2+4y-y+5z-1=
-x-3x-2y-4y+4y-y+3z+5z+5z-4-2-1=
-4x-3y+13z-7

b)
2*(3x+2y-4z+5)+3(5x-8y+2z-1)+(4x-2y+7z+8)=
6x+4y-8z+10+15x-24y+6z-3+4x-2y+7z+8=
6x+15x+4x+4y-24y-2y-8z+6z+7z+10-3+8=
25x-22y+5z+15